2022
DOI: 10.3390/life12081148
|View full text |Cite
|
Sign up to set email alerts
|

Docking and Molecular Dynamics Study to Identify Novel Phytobiologics from Dracaena trifasciata against Metabolic Reprogramming in Rheumatoid Arthritis

Abstract: Enhancement of glycolysis and glutaminolysis are the two most common modalities associated with metabolic reprogramming in rheumatoid arthritis (RA). This enhancement is concomitant to the upregulation of hexokinase 2 (HK2) and glutaminase 1 (GLS1). Hence, the current study was undertaken to identify potential phytobiological inhibitors against HK2 and GLS1, from Dracaena (Sansevieria) trifasciata, an indigenous ethnomedicinal plant found in Pakistan, using computational analysis. Phytobiologics from Dracaena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Rheumatoid Arthritis (RA) is a prevalent autoimmune disease affecting humans, with a global predominance of approximately 1%. [1]. It is an inflammatory disease in which the immune system of the body attacks healthy cells by mistake causing painful swelling in the affected body parts [2].…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid Arthritis (RA) is a prevalent autoimmune disease affecting humans, with a global predominance of approximately 1%. [1]. It is an inflammatory disease in which the immune system of the body attacks healthy cells by mistake causing painful swelling in the affected body parts [2].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [ 20 ], we discovered novel compounds with the potential of dual inhibition of key enzymes of glycolysis and glutaminolysis, i.e., HK2 and GLS. Computational assessment revealed that 28MS inhibits both target enzymes similarly.…”
Section: Introductionmentioning
confidence: 99%